2021
DOI: 10.1186/s13195-021-00783-x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized crossover trial of a modified ketogenic diet in Alzheimer’s disease

Abstract: Background Brain energy metabolism is impaired in Alzheimer’s disease (AD), which may be mitigated by a ketogenic diet. We conducted a randomized crossover trial to determine whether a 12-week modified ketogenic diet improved cognition, daily function, or quality of life in a hospital clinic of AD patients. Methods We randomly assigned patients with clinically confirmed diagnoses of AD to a modified ketogenic diet or usual diet supplemented with lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(127 citation statements)
references
References 37 publications
4
123
0
Order By: Relevance
“…Although this particular manuscript aims to focus on disease prevention, it is worth noting that dietary interventions that increase βhB have shown to be effective at improving symptoms in individuals with AD, in part, by supplying an alternative source of fuel, as opposed to glucose, to the brain [77][78][79]. For example, a recent randomized controlled crossover trial comparing a 12-week ketogenic diet to a 12-week low-fat diet found that the former caused significant improvements in daily functioning and overall quality of life as compared to the latter [80]. We choose to comment briefly on these symptom data both to further the rationale for providing a ketogenic option to at-risk patients and to acknowledge that there is a lack of consensus over whether ApoE4 carriers constitute a less responsive group to ketogenic therapy.…”
Section: Ketogenic Diets and β-Hydroxybutyratementioning
confidence: 99%
“…Although this particular manuscript aims to focus on disease prevention, it is worth noting that dietary interventions that increase βhB have shown to be effective at improving symptoms in individuals with AD, in part, by supplying an alternative source of fuel, as opposed to glucose, to the brain [77][78][79]. For example, a recent randomized controlled crossover trial comparing a 12-week ketogenic diet to a 12-week low-fat diet found that the former caused significant improvements in daily functioning and overall quality of life as compared to the latter [80]. We choose to comment briefly on these symptom data both to further the rationale for providing a ketogenic option to at-risk patients and to acknowledge that there is a lack of consensus over whether ApoE4 carriers constitute a less responsive group to ketogenic therapy.…”
Section: Ketogenic Diets and β-Hydroxybutyratementioning
confidence: 99%
“…In the modified Mediterranean-ketogenic diet (Med-KD), carbohydrates, fat, and protein provide less than 10%, 60-65%, and 30-35% of energy, respectively [8]. Researchers from New Zealand have used another KD plan, which provides an average macronutrient ratio of 58% fat (26% saturated, 32% non-saturated), 29% protein, 7% fiber, and 6% net carbohydrates by weight [9]. The main fat sources in these ketogenic diets are long-chain fatty acids.…”
Section: Ketogenic Diet Characteristicsmentioning
confidence: 99%
“…In a recently published randomized crossover trial, Phillips et al [9] determine whether a 12-week modified KD improved cognition, daily function, or quality of life in a hospital clinic of AD patients. Patients achieved sustained physiological ketosis.…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ketogenic diets (KD) have a near century long history of being used to treat pediatric epilepsy ( 7 ), and newer research is beginning to explore their therapeutic potential in other chronic disease, such as type II diabetes ( 8 , 9 ), polycystic ovarian syndrome ( 10 ), Alzheimer's disease ( 11 ), Parkinson's disease ( 12 ), cardiovascular risk ( 13 ), metabolic syndrome ( 14 ), and various mental illnesses ( 15 ). Many of these disease have an inflammatory component and, correspondingly, well-formulated ketogenic diets have been shown to improve a broad spectrum of inflammatory markers ( 16 ).…”
Section: Introductionmentioning
confidence: 99%